STRATEGI PENINGKATAN RESPONSIVITAS CUSTOMER SUPPORT DI PT CLOUD HOSTING INDONESIA UNTUK KEPUASAN PELANGGAN - Ika, Ika; Kamdan, Kamdan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze strategies for improving the responsiveness of customer support services at PT Cloud Hosting Indonesia to enhance customer satisfaction. Methods include qualitative analysis with data gathered through interviews, observations, and surveys. Results show the effectiveness of implementing AI-based chatbots, structured employee training, and integrated ticketing systems in reducing response times and increasing customer satisfaction. This study provides actionable insights for improving customer support in the cloud hosting industry.